The relationship between body mass index and sleep in women with risk factors for gestational diabetes mellitus - Pamela Acosta Reyes; Jincy Immanuel; William M. Hague; Helena Teede; Emily Hibbert; Christopher J. Nolan; Michael J. Peek; Vincent Wong; Jeffrey R. Flack; Mark McLean; Raiyomand Dalal; Jürgen Harreiter; et al. (Wiley, 2023)
Abstract Background Both obesity and sleep disorders are common among women during pregnancy. Although prior research has identified a relationship between obesity and sleep disorders, those findings are from women later in pregnancy. Objective To explore the relationships between self‐reported sleep duration, insufficient sleep and snoring with body mass index (BMI) among multiethnic women at risk of gestational diabetes mellitus (GDM)in early pregnancy. Methods Cross‐sectional study of baseline data from women at risk of GDM enrolled in the Treatment of BOoking Gestational diabetes Mellitus (TOBOGM) multicentre trial across 12 Australian/Austrian sites. Participants completed a questionnaire before 20 weeks' gestation to evaluate sleep. BMI <25 kg/m2 served as the reference group in multivariable logistic regression. Results Among the 2865 women included, the prevalence of overweight and obesity classes I‐III was 28%, 19%, 11% and 12%, respectively. There was no relationship between sleep duration and BMI. The risk of insufficient sleep >5 days/month was higher in class II and class III obesity (1.38 (1.03-1.85) and 1.34 (1.01-1.80), respectively), and the risk of snoring increased as BMI increased (1.59 (1.25-2.02), 2.68 (2.07-3.48), 4.35 (3.21-5.88) to 4.96 (3.65-6.74), respectively)). Conclusions Obesity is associated with insufficient sleep among pregnant women at risk of GDM. Snoring is more prevalent with increasing BMI.